Involvement of Histamine Released From Mast Cells in Acute Radiation Dermatitis in Mice - Saiko Moriyasu; Kouichi Yamamoto; Naoko Kureyama; Keita Okamura; Toshiji Ikeda; Atsushi Yamatodani (Elsevier, 2007)
A possible involvement of histamine in acute radiation dermatitis in mice was investigated. The dose of 40 Gy of gamma irradiation induced erythema and edema in C57BL/6 mice treated with vehicle. However, in C57BL/6 mice treated with chlorpheniramine and WBB6F1-W/Wv mice, erythema and edema were not observed. In all of these mice, epilation and dry desquamation were induced, but bepotastine significantly reduced the extent of these areas. These results suggest that gamma irradiation-induced erythema and edema were caused by histamine released from mast cells via histamine H1 receptor, and epilation was induced by other inflammatory mediators. Keywords:: radiation dermatitis, histamine, mast cell